Analysis of Bullying Behavior in Junior High Schools in Batusangkar City - Rafsel Tas'adi; Dasril Dasril; Romi Fajar Tanjung; Silvi Andeslin; Nadia Purnama Sari (Electronic Journal of Education, Social Economics and Technology, 2025)
Bullying is a negative behavior that can be done directly or indirectly with the aim of hurting someone physically and psychologically. Assistance interventions need to be given to both victims and perpetrators, because both are teenagers who need to be guided and assisted so that they have a good identity and future. The purpose of this study was to identify bullying behavior that is often experienced by students in junior high schools in Batusangkar City. The sampling technique used the cluster sampling technique and obtained a research sample of 150 students. Data collection used the Guttman bullying scale in junior high schools. Data analysis used the Excel application to assist in classifying bullying behavior groups. The research findings showed that the highest level of bullying categories were verbal bullying and physical bullying. The results of this study can be used to reduce bullying behavior and prevent more severe impacts due to physical bullying, verbal bullying, cyber bullying and relational bullying.